Silicon negative electrode material for solid-state battery and preparation method of silicon negative electrode material

By constructing an elastic electron-ion dual-conductive cladding on the nano-silicon surface, the problem of limited conduction of silicon-based anode material is solved, and the lithium ion and electron conduction performance is improved under low pressure, reducing the difficulty and cost of battery assembly.

CN119208554APending Publication Date: 2024-12-27WANXIANG 123 CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411270280.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The lithium ion and electron conduction of silicon-based anode materials in existing all-solid-state lithium-ion batteries is limited, resulting in volume expansion and extrusion, increasing the difficulty of battery assembly and production costs, and requiring large applied pressure to optimize charge transfer.

Method used

Through spray thermal polymerization technology, an elastic electron-ion double-conductive polymer solid electrolyte coating is constructed on the nano-silicon surface, reducing the interfacial charge transfer impedance, and improving the compressibility of the material through the combination of polymer and conductive carbon materials and Deformation capability, buffer volume expansion and tightly compact powder particles.

Benefits of technology

Achieve tight solid contact inside the pole sheet under low applied pressure, improve lithium ion and electron conduction performance, extend battery life and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208554A_ABST
    Figure CN119208554A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a silicon negative electrode material for a solid-state battery and a preparation method of the silicon negative electrode material. The preparation method of the silicon negative electrode material for the solid-state battery comprises the following steps: by taking micron silicon as a raw material, obtaining nano silicon particles by adopting a liquid-phase sanding method, and then carrying out spray thermal polymerization and drying granulation treatment on precursor slurry by using a spray dryer, thereby obtaining the silicon negative electrode material for the solid-state battery. Carrying out in-situ polymerization on the surface of the nano silicon to construct an elastic electron-ion dual-conductive polymer solid electrolyte coating layer; the obtained nanometer silicon composite material realizes excellent solid-solid contact in the pole piece and between the pole piece and a solid electrolyte interlayer under low external pressure, and interface charge transfer impedance is reduced; in addition, the elastic coating layer has good compressibility and deformability, effectively buffers the lithium intercalation volume of nano silicon, even can increase the internal stress of the pole piece by means of expansion, compactly compact powder particles in the negative electrode, and improve the electron and ion transmission of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon negative electrode material for solid-state batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries dominate the battery consumer market due to their high energy density, long cycle life, and no memory effect. To date, lithium-ion batteries have been commercially used and still mainly use liquid organic electrolytes. However, the energy density of traditional liquid lithium-ion batteries is close to the theoretical upper limit, and safety is also challenged, with battery fires occurring from time to time. Therefore, in order to improve safety and extend battery life, it has become an industry consensus to replace flammable organic electrolytes with solid electrolytes with higher mechanical strength and promote the development of solid-state lithium batteries.

[0003] Silicon-based materials are considered to be the next generation of electrochemical energy storage anodes. They are abundant in reserves, have a high theoretical specific capacity (3600mAh / g), and have an average lithium insertion potential of 0.4V (vs.Li + / Li), dendrite growth is not likely to occur, and the whole battery can maintain a relatively high operating voltage. Therefore, the combination of silicon-based anode and solid electrolyte to construct an all-solid-state lithium-ion battery can effectively improve the energy density and safety of the whole battery.

[0004] Existing all-solid-state batteries are mainly divided into dry powder pressed powder cake, wet coating, dry film and thin film all-solid-state batteries according to the preparation technology. Since silicon-based materials are poor conductors of electrons and lithium ions, in order to improve the lithium ion and electron conduction in the all-silicon negative electrode, it is necessary to mix and compound conductive agents and solid electrolyte powders, and tighten the solid-solid contact between powder particles through external pressure. In addition, the researchers constructed polymer, hard carbon, and transition metal coating layers on the surface of the silicon negative electrode to buffer the volume expansion of the silicon negative electrode, avoid silicon particle powder, and at the same time make the silicon-based materials have better lithium ion and electron conduction, thereby extending the capacity and cycle life of the whole battery.

[0005] The all-silicon negative electrode in the solid-state battery system requires silicon, solid electrolyte and conductive agent to be mechanically mixed before being made into sheets. Therefore, the solid-solid contact surface between the rigid particles in the electrode is small or even only point contact, resulting in limited local lithium ion and electron conduction, leading to increased polarization. The lithium embedding process of silicon-based materials is accompanied by huge volume expansion, which causes squeezing between rigid particles and causes silicon particles to break and pulverize. In addition, at this stage, solid-state batteries usually need to be subjected to a large external pressure (up to tens or even hundreds of MPa) during operation to optimize the charge transfer between particles inside the solid-state negative electrode sheet and on the solid-solid interface between the solid electrolyte sheet. However, this undoubtedly increases the process difficulty and production cost of battery assembly and preparation. Summary of the invention

[0006] The present invention provides a silicon negative electrode material for solid-state batteries and a preparation method thereof, the purpose of which is: on the one hand, by spraying thermal polymerization and drying granulation treatment of the precursor slurry, in-situ polymerization is constructed on the surface of nano-silicon to form an elastic electron-ion dual conductive polymer solid electrolyte coating layer, so that the nano-silicon composite material can be easily contacted with each other, and the interface charge transfer impedance is reduced; on the other hand, the elastic coating layer has good compressibility and deformation ability, effectively buffers the lithium embedded volume of the nano-silicon, and can even increase the internal stress of the pole piece by expansion, tightly compact the powder particles in the negative electrode, and improve the electron and ion transmission of the solid-state battery.

[0007] Technical solution:

[0008] In the first aspect, the present application provides a silicon negative electrode material for a solid-state battery:

[0009] A silicon negative electrode material for a solid-state battery comprises a nano silicon material and an elastic coating layer attached to the surface of the nano silicon material, wherein the elastic coating layer comprises a polymer, a lithium salt and a conductive carbon material.

[0010] Furthermore, the nano silicon particle size D50 is 50-150 nm.

[0011] Furthermore, the particle size D50 of the silicon negative electrode material for solid-state batteries is 5 to 20 μm.

[0012] In a second aspect, the present application provides a method for preparing a silicon negative electrode material for a solid-state battery:

[0013] A method for preparing a silicon negative electrode material for a solid-state battery, wherein the elastic coating layer is prepared by spray thermal polymerization of a mixed slurry including a polymer monomer, a lithium salt and a conductive carbon material under the action of an initiator, and the polymer monomer undergoes a polymerization reaction to prepare a polymer.

[0014] Furthermore, the method for preparing the silicon negative electrode material for solid-state batteries comprises the following steps:

[0015] S1: Micron silicon is used as raw material, dispersed in ethanol, and the silicon is crushed into nano silicon by sand milling to obtain nano silicon slurry;

[0016] S2: adding conductive carbon material, lithium salt and polymer monomer to the nano-silicon slurry in sequence, mixing them evenly, and preparing a mixed slurry;

[0017] S3: Add an initiator to the mixed slurry, mix evenly, use an inert gas as a carrier gas, perform spray thermal polymerization and dry granulation to obtain a silicon negative electrode material for a solid-state battery.

[0018] In view of the shortcomings of the prior art and the applicable requirements of all-solid-state lithium-ion batteries, the present invention designs a silicon-based negative electrode material with an elastic electron-ion dual conductive coating layer and a preparation method thereof. First, the micron silicon is crushed into nano silicon by liquid phase sand milling using an ethanol undispersed phase, and then lithium salt, polymer monomer, initiator, and conductive carbon material are sequentially added to the nano silicon slurry. Finally, the mixed slurry is stirred evenly and then subjected to a spray thermal polymerization process to complete the monomer polymerization, drying, and granulation steps in one step, thereby obtaining a silicon-based material with an elastic electron-ion dual conductive coating layer.

[0019] The present invention uses micron silicon as raw material and adopts liquid phase sand milling method to obtain nano silicon particles. Subsequently, the precursor slurry is subjected to spray thermal polymerization and dry granulation treatment by a spray dryer, and an elastic electron-ion dual conductive polymer solid electrolyte coating layer is constructed by in-situ polymerization on the surface of the nano silicon. The obtained nano silicon composite material realizes excellent solid-solid contact inside the pole piece and between the pole piece and the solid electrolyte separator under low external pressure, and reduces the interfacial charge transfer impedance. In addition, the elastic coating layer has good compressibility and deformation ability, effectively buffers the lithium embedded volume of the nano silicon, and can even increase the internal stress of the pole piece by expansion, tightly compact the powder particles in the negative electrode, and improve the electron and ion transmission of the solid-state battery.

[0020] The polymer matrix in the coating layer undergoes elastic deformation at relatively low pressure, which greatly increases the effective contact area between the particles inside the electrode and between the electrode and the solid electrolyte. At the same time, since the elastic polymer helps to buffer the lithium-inserted expansion of nano-silicon and fill the pores between the particles through deformation, on the other hand, the controllable expansion of the particles can also increase the internal stress, thereby making the solid-solid contact between the particles closer, improving the lithium ion and electron conduction at the interface, and improving the rate performance of silicon negative electrode materials. The polar groups (-OH, -O-, etc.) in the polymer not only combine with the hydroxyl groups on the silicon surface to improve the uniformity of the coating, but also combine with the anions (TFSI) in the lithium salt. - , ClO4 - In addition, the spray thermal polymerization process greatly shortens the process flow of silicon-based material preparation and realizes the controllable preparation of silicon-based negative electrode materials with concentrated particle size and uniform dispersion of multiple components.

[0021] Compared with silicon negative electrode materials that only use conductive materials, in the present application, conductive materials such as single-walled carbon nanotubes with a relatively large aspect ratio are used in polymers to be matched with lithium salts; lithium salts can interact with polar groups on polymer molecular chains to reduce the mobility of molecular chains, and are matched with conductive materials such as single-walled carbon nanotubes with a relatively large aspect ratio, thereby improving the strength and hardness of the polymer, and are matched with spray thermal polymerization. On the one hand, a silicon negative electrode material for solid-state batteries with a relatively small particle size is prepared, and the elastic coating layer in the silicon negative electrode material for solid-state batteries can be well coated on the surface of the nano silicon material; further, the solid Silicon negative electrode materials for batteries do not require further sand grinding or ball milling, and the elastic coating layer on the surface of nano-silicon will not be destroyed. The complete elastic coating layer on the surface can better protect the nano-silicon and reduce the powderization of nano-silicon during the volume expansion of the silicon negative electrode, thereby improving the solid-solid contact in the negative electrode material and improving the conduction of lithium ions and electrons. On the other hand, conductive materials such as single-walled carbon nanotubes with a relatively large aspect ratio are used in polymers in combination with lithium salts. Lithium salts can act as electrolytes to form ion channels in polymers, thereby changing the electrical properties of the polymer such as electrical conductivity and dielectric constant, thereby improving the electrical performance of the battery.

[0022] Furthermore, the conductive carbon material is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, acetylene black and graphene, and the amount of the conductive carbon material added is 10 to 40 wt% of the amount of nano-silicon used; the lithium salt is any one of LiTFSI, LiFSI, LiClO4 and LiPF6, and the amount of the lithium salt added is 5 to 20 wt% of the amount of nano-silicon used.

[0023] Furthermore, the polymer monomer is one or more of polyethylene glycol lithium diacrylate, lithium acrylate, methyl acrylate and methyl methacrylate, and the added amount of the polymer monomer is 10-40wt% of the amount of nano-silicon used.

[0024] Furthermore, the initiator is one or more of potassium persulfate, azobisisobutyronitrile, and hydrogen peroxide, and the added amount of the initiator is 0.5 to 2 wt % of the polymer monomer.

[0025] Furthermore, the inert gas is one of nitrogen, argon and helium.

[0026] Furthermore, the process parameters of the spray thermal polymerization in step S3 include: an air inlet temperature of 150 to 250° C., an air outlet temperature of 75 to 150° C., and a creeping flow rate of 0.1 to 10 L / h.

[0027] Compared with the prior art, this application has the following beneficial effects:

[0028] 1) Liquid phase sand milling is used to nano-size silicon powder, and the elastic coating layer containing lithium salt is well coated on the surface of the nano-silicon material, shortening the electron and ion transmission path, while inhibiting the breakage and pulverization of nano-silicon particles.

[0029] 2) The in-situ polymerization coating of nano-silicon is carried out by the spray thermal polymerization process, which helps to improve the contact between nano-silicon and the solid electrolyte. The elastic coating layer containing lithium salt is better coated on the surface of the nano-silicon material, thereby improving the diffusion of lithium ions on the solid-solid interface.

[0030] 3) Construct an elastic coating on the surface of nano-silicon to improve the mechanical strength and conductivity of the elastic coating, increase the contact area between silicon particles and between the negative electrode sheet and the solid electrolyte under low or even no external pressure, and thus improve the electrical performance of batteries using silicon negative electrode materials for solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the structure of the silicon negative electrode material for the solid-state battery of Example 1.

[0032] Figure 2 This is a schematic diagram of the structure of the silicon negative electrode material for the solid-state battery of Example 1. DETAILED DESCRIPTION

[0033] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the specific embodiments of the accompanying drawings.

[0034] Example 1

[0035] A silicon negative electrode material for solid-state batteries, the preparation method of which is as follows:

[0036] S1: Nano-silicon sand milling: 1 kg of micron silicon was dispersed in 9 kg of ethanol to prepare a 10 wt% slurry, stirred and dispersed for 60 min, and then added to a sand mill for sand milling to obtain a nano-silicon slurry containing nano-silicon with a particle size (D50) of 100 nm;

[0037] S2: Material mixing: 200 g of single-walled carbon nanotubes (solid content of the slurry is 2 wt.%, length 5-10 μm), 100 g of LiTFSI and 300 g of lithium acrylate are added to the nano-silicon slurry prepared in step S1 in sequence, and stirring is continued for 30 min until the components are evenly mixed to prepare a mixed slurry.

[0038] S3: Spray thermal polymerization: 3 g of azobisisobutyronitrile was added to the mixed slurry prepared in step S2, and the mixture was uniformly mixed and then transported to a spray dryer by a peristaltic pump. The feed rate was controlled at 5 L / h, the air inlet temperature was set to 200° C., and the air outlet temperature was set to 150° C. to prepare a silicon negative electrode material for a solid-state battery. The structural schematic diagram of the silicon negative electrode material for a solid-state battery is shown in FIG. Figure 1 .

[0039] Experimental Example 2

[0040] A silicon negative electrode material for solid-state batteries, the preparation method of which is as follows:

[0041] S1: Nano-silicon sand milling: 1 kg of micron silicon was dispersed in 9 kg of ethanol to prepare a 10 wt% slurry, stirred and dispersed for 60 min, and then added to a sand mill for sand milling to obtain nano-silicon with a particle size (D50) of 80 nm.

[0042] S2: Material mixing: 300 g of carbon nanofibers, 50 g of LiPF6 and 200 g of polyethylene glycol lithium diacrylate were added to the nano-silicon slurry prepared in step (1) in sequence, and the mixture was stirred for 30 min until the components were evenly mixed to obtain a mixed slurry.

[0043] S3: Spray thermal polymerization: Add 4 g of potassium persulfate to the mixed slurry prepared in step S2, mix well and transport to the spray dryer with a peristaltic pump. The feed rate is controlled at 2 L / h, the inlet air temperature is set to 180°C, and the outlet air temperature is set to 120°C to prepare silicon negative electrode material for solid-state batteries.

[0044] Experimental Example 3:

[0045] A silicon negative electrode material for solid-state batteries, the preparation method of which is as follows:

[0046] S1: Nano-silicon sand milling: 1 kg of micron silicon was dispersed in 9 kg of ethanol to prepare a 10 wt% slurry, stirred and dispersed for 60 min, and then added to a sand mill for sand milling to obtain nano-silicon with a particle size (D50) of 150 nm.

[0047] S2: Material mixing: 200 g (solid mass) of graphene slurry, 150 g of LiClO4 and 200 g of methyl methacrylate were added to the nano-silicon slurry prepared in step S1 in sequence, and stirring was continued for 30 min until the components were evenly mixed to prepare a mixed slurry.

[0048] S3: Spray thermal polymerization: Add 4 g of azobisisobutyronitrile to the mixed slurry prepared in step S2, mix well and transport to the spray dryer with a peristaltic pump. The feed rate is controlled at 8 L / h, the inlet air temperature is set to 250°C, and the outlet air temperature is set to 180°C to prepare silicon negative electrode material for solid-state batteries.

[0049] Comparative Example 1:

[0050] A silicon negative electrode material for solid-state batteries, the preparation method of which is as follows:

[0051] S1: Spray thermal polymerization: 100g LiTFSI and 300g lithium acrylate were dispersed in 2kg ethanol, stirred evenly, and then 2g azobisisobutyronitrile was added. After mixing evenly, the mixture was fed to a spray dryer via a peristaltic pump at a feed rate of 2L / h. The feed rate was controlled at 2L / h, the inlet air temperature was set to 200°C, and the outlet air temperature was set to 150°C to prepare a polymer solid electrolyte powder;

[0052] S2: Material mixing: 500g of sand-ground nano-silicon powder, 150g of acetylene black and 150g of the above-mentioned polymer solid electrolyte powder are placed in a high-speed ball mill for grinding and mixing for 6 hours to prepare a silicon negative electrode material for a solid-state battery. The structural schematic diagram of the silicon negative electrode material for a solid-state battery is shown in Figure 2 .

[0053] Comparative Example 2:

[0054] A silicon negative electrode material for solid-state batteries, the preparation method of which is as follows:

[0055] Material mixing: 500 g of sand-ground nano-silicon powder, 150 g of multi-walled carbon nanotubes and 150 g of lithium aluminum titanium phosphate (LATP) electrolyte powder were placed in a high-speed ball mill for grinding and mixing for 6 hours to prepare a silicon negative electrode material for solid-state batteries.

[0056] The silicon negative electrode materials described in Examples 1-3 and Comparative Examples 1 and 2 were assembled into solid-state half-cells and subjected to electrochemical performance tests. The experimental results are shown in Table 1. The specific test scheme is as follows:

[0057] Solid-state half-cell assembly and electrochemical performance test: 100mgLi6PS5Cl solid electrolyte powder was pre-pressed at 1t, then 2mg composite negative electrode powder was evenly dispersed on one side, and the pressure was maintained at 7t for 3min, and then on the other side, In foil and Li foil were attached in sequence, and then the pressure was maintained at 3t for about 1min, and then the screws of the battery mold were tightened to obtain a solid-state half-cell. The solid-state half-cell was tested at room temperature, the voltage window was set to 0.005~1.5V, and the test rate was set to 0.1C (2C).

[0058] Table 1. Test results of electrochemical performance of solid-state half-cells using silicon negative electrode materials for solid-state batteries of Examples 1-3 and Comparative Examples 1-2

[0059] Material First lithium removal capacity (0.1C; mAh / g) 100-cycle retention rate (%) Lithium removal capacity (2C; mAh / g) Example 1 2317 75.7 1736 Example 2 2265 73.3 1701 Example 3 2008 71.1 1533 Comparative Example 1 1633 54.2 995 Comparative Example 2 1470 48.0 873

[0060] From the data obtained from the solid-state half-cell test, it can be found that the polymer solid electrolyte coating layer on the surface of the nano-silicon composite material helps to strengthen the solid-solid contact between particles in the negative electrode plate, buffer the volume expansion of nano-silicon embedded lithium, and stabilize the electrode structure, thereby significantly improving the first-cycle lithium delithiation capacity and Coulomb efficiency of the silicon-carbon composite material and improving the cycle stability of the material.

[0061] The above embodiments are all preferred embodiments of the present invention, which are only used to specifically illustrate the scheme of the present invention and should not be regarded as limiting the present invention. For those skilled in the art, various improvements and optimizations can be made without departing from the technical principles of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the invention should be included in the protection scope of the present invention.

[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A silicon negative electrode material for solid-state batteries, characterized in that: The invention comprises a nano silicon material and an elastic coating layer attached to the surface of the nano silicon material, wherein the elastic coating layer comprises a polymer, a lithium salt and a conductive carbon material.

2. The silicon negative electrode material for solid-state batteries according to claim 1, characterized in that: The nano silicon particle size D50 is 50-150 nm.

3. The silicon negative electrode material for solid-state battery according to claim 1, characterized in that: The particle size D50 of the silicon negative electrode material for solid-state batteries is 5 to 20 μm.

4. A method for preparing the silicon negative electrode material for solid-state batteries according to any one of claims 1 to 3, characterized in that: The elastic coating layer is prepared by spray thermal polymerization of a mixed slurry including polymer monomers, lithium salts and conductive carbon materials under the action of an initiator, and the polymer monomers undergo a polymerization reaction to prepare a polymer.

5. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 4, characterized in that: The following steps are involved: S1: Micron silicon is used as raw material, dispersed in ethanol, and the silicon is crushed into nano silicon by sand milling to obtain nano silicon slurry; S2: adding conductive carbon material, lithium salt and polymer monomer to the nano-silicon slurry prepared in S1 in sequence, mixing them evenly, and preparing a mixed slurry; S3: adding an initiator to the mixed slurry prepared in S2, mixing evenly, and using an inert gas as a carrier gas to perform spray thermal polymerization and dry granulation to obtain a silicon negative electrode material for a solid-state battery.

6. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 5, characterized in that: The conductive carbon material is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, acetylene black and graphene, and the amount of the conductive carbon material added is 10 to 40 wt% of the amount of nano-silicon used; the lithium salt is any one of LiTFSI, LiFSI, LiClO4 and LiPF6, and the amount of the lithium salt added is 5 to 20 wt% of the amount of nano-silicon used.

7. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 5, characterized in that: The polymer monomer is one or more of polyethylene glycol lithium diacrylate, lithium acrylate, methyl acrylate and methyl methacrylate, and the added amount of the polymer monomer is 10-40wt% of the amount of nano-silicon used.

8. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 5, characterized in that: The initiator is one or more of potassium persulfate, azobisisobutyronitrile and hydrogen peroxide, and the added amount of the initiator is 0.5-2wt% of the polymer monomer.

9. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 5, characterized in that: The inert gas is one of nitrogen, argon and helium.

10. The method for preparing a silicon negative electrode material for a solid-state battery according to claim 5, characterized in that: The process parameters of the spray thermal polymerization in step S3 include: an air inlet temperature of 150 to 250° C., an air outlet temperature of 75 to 150° C., and a creeping flow rate of 0.1 to 10 L / h.

Citation Information

Cited By

  • Polymer-coated positive electrode material and preparation method thereof, positive electrode plate and solid-state battery

    CN121076097A